Meningkatan Hasil Belajar PAKBP Melalui Pembelajaran PBL pada Materi Aku Pribadi yang Unik Kelas IV SDS Dakwatul Islam - Desi Lestaria Br Sitepu; Yohanes Subasno; Veronika Sunarningsih (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research is conducted with the aim of improving the learning outcomes of students by using the Problem-Based Learning (PBL) model for the students in grade IV Phase B of SDS DAKWATUL ISLAM in the academic year 2023/2024.